Morphological evidence by scanning electron microscopy of excretion of metacyclic forms of Trypanosoma cruzi in vector's urine - Rodrigo Zeledon; Rodolfo Bolaños; M. R. Espejo Navarro; Miguel Rojas (Memorias do Instituto Oswaldo Cruz, 1988)
Comparision by scanning electron microscopy (SEM) of Trypanosoma cruzi flagellates attached to the cuticle of the rectal gland of infected Dipetalogaster maxima nymphs, showed marked differences before amd after feeding. Before feeding numerous metacyclic trypomastigotes were observed among the abundant epimastigotes that formed the carpet of flagellates. On the other hand, in insects that were allowed to urinate for 24 hours after a meal, the metacyclics were scarce,indicating that they had been detached by the urine flow. An asymetric type of cell division, probably originating both an epi-and a trypomastigote, was occasionally observed. The occurrence of swellings at different levels of the flagella of epimastigotes suggests that secondary sites of attachment may be common. Observando-se, em microscopia eletrônica de varedura, formas flageladas do Trypanosoma cruzi presas a cutícula da glândula retal de ninfas infectadas de Dipetalogaster maxima verificaram-se nítidas diferenças antes e depois da alimentação. Antes, viam-se numerosos tripomastigotas metacíclicos entre os abundantes epimastigotas que formavam o tapete de flagelados, ao passo que nos insetos que urinavam dentro das 24 horas após o repasto os metacíclicos eram raros, indicando que haviam sido desprendidos pelo fluxo urinário. Foi notado, as vezes, um tipo assimétrico de divisão celular, originando um epi e um tripomastigota. Nos flagelados dos epimastigotas a presença de dilatações a diferentes níveis sugere que lugares secundários de aderência podem ser comuns.